Optimalisasi CRM Digital Mykonos Parfum: Eksplorasi Persepsi Pelanggan dan Strategi Penguatan pada Platform E-Commerce - Nurmiati, Evy; Wicaksono, Bayu (Forum Kerjasama Pendidikan Tinggi, 2025)
The growth of e-commerce has driven local brands such as Mykonos Parfum to optimize their Customer Relationship Management (CRM) strategies in order to maintain customer loyalty on digital platforms, particularly Shopee. This study aims to explore customer perceptions of the effectiveness of Mykonos's CRM implementation through a descriptive-exploratory qualitative approach. Data were collected from 80 purposively selected customer reviews and manually analyzed using thematic content analysis with the aid of Microsoft Excel and Google Docs. The results indicate that responsiveness in communication is the most appreciated aspect, while delivery delays, difficult return processes, and limited stock availability remain key weaknesses. Nevertheless, customer loyalty remains high, influenced by perceptions of exclusivity and emotional attachment to the brand. This study recommends strengthening CRM systems through improved logistics management, simplified after-sales services, and the utilization of cross-platform digital interactions. The main contribution of this study lies in the development of digital engagement practices within a strategic CRM framework for the local e-commerce sector, emphasizing the importance of integrating operational, emotional, and symbolic dimensions in fostering affective loyalty. The study also suggests future research using a mixed-method approach and cross-channel digital analysis to broaden the understanding of consumer behavior.